Blood Pressure and Mortality in Long-Term Hemodialysis—Time to Move Forward. (22nd September 2016) - Georgianos, Panagiotis I.; Agarwal, Rajiv
Abstract: Contrary to the direct, graded, and causal relationship of hypertension with cardiovascular outcomes in the general population, among dialysis patients, blood pressure (BP) recorded either predialysis or postdialysis displays a U-shaped curve with mortality. This paradoxical phenomenon of lower BP or a decline in BP over time being associated with increased mortality and higher BP being associated with a lower mortality is described as "reverse" epidemiology of hypertension, raising substantial controversy on whether BP lowering causes harms or benefits among dialysis patients. Unlike the inverse relationship of peridialytic BP with mortality, elevated BP recorded outside of dialysis is directly associated with poor long-term outcomes. Apart from the timing and technique of BP measurement, the U-shaped association of BP with mortality is also modified when accounting for factors related to patient's clinical characteristics and level of illness, dialysis practices, and patterns as well as factors related to the methodology of survival analysis. Most importantly, deliberate BP lowering with antihypertensive drugs is associated with reduced cardiovascular morbidity and mortality. In this review, we explore the complex association of peridialytic, intradialytic, and interdialytic BP with outcomes among dialysis patients. We conclude with recommendations for a wider use of out-of-dialysis BP monitoring as a tool to better evaluate the cardiovascular risk and optimize the management of hypertension in this high-risk population. Rather than more cohort studies, we call for randomized trials to test the level of BP in dialysis patients that is optimal for cardiovascular outcomes.